Acquisition of IGG to ICAM-1-Binding DBLΒ Domains in the plasmodium falciparum erythrocyte membrane protein 1 antigen family varies between groups A, B, and C - Ecklu-Mensah, G.; Olsen, R.W.; Bengtsson, A.; Ofori, M.F.; Kusi, K.A.; Koram, K.A.; Hviid, L.; Adams, Y.; Jensen, A.T.R. (Infection and Immunity, 2019)
Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) is an important malaria virulence factor. The protein family can be divided into clinically relevant subfamilies. ICAM-1-binding group A PfEMP1 proteins also bind endothelial protein C receptor and have been associated with cerebral malaria in children. IgG to these PfEMP1 proteins is acquired later in life than that to group A PfEMP1 not binding ICAM-1. The kinetics of acquisition of IgG to group B and C PfEMP1 proteins binding ICAM-1 is unclear and was studied here. Gene sequences encoding group B and C PfEMP1 with DBL domains known to bind ICAM-1 were used to identify additional binders. Levels of IgG specific for DBL domains from group A, B, and C PfEMP1 binding or not binding ICAM-1 were measured in plasma from Ghanaian children with or without malaria. Seven new ICAM-1-binding DBL domains from group B and C PfEMP1 were identified. Healthy children had higher levels of IgG specific for ICAM-1-binding DBL domains from group A than from groups B and C. However, the opposite pattern was found in children with malaria, particularly among young patients. Acquisition of IgG specific for DBL domains binding ICAM-1 differs between PfEMP1 groups.
Research Article
Keywords: PfEMP1; Plasmodium falciparum; antibodies; immunity; malaria